Reimagining U.S. Olympic sports - How the Covid-19 pandemic serves as the catalyst for public funding, greater transparency, and increased athlete rights - Conrad, M. A. (SSRN, 2020)
The Amateur Sports Act was enacted over four decades ago when Olympic sports were still an "amateur" pursuit. That law created a self-funding system for the United States Olympic and Paralympic Committee and the national governing bodies for the respective Olympic sports. Its self-governance model resulted in a system of limited transparency and ineffective governance that culminated with the sex abuse scandals involving young athletes. With the growth and change in the now U.S. Olympic and Paralympic movement over the last four decades, this article advocates significant changes to the law to permit direct or indirect government funding for the United States Olympic and Paralympic Committee (USOPC) and the sport governing bodies in return for more stringent transparency and ethical rules. The new law should "federalize" a new governing body that will oversee the USOPC and the governing bodies and create additional rights for rights for athletes and required disclosure and ethics rules for the Olympic bodies. Because of the Covid pandemic and the funding shortfalls faced by the USOPC and the governing bodies, the article concludes that now is the time for such a major change.